Analisis Kelayakan Finansial Dan Sensitivitas Usahatani Anggur Di Desa Banjar Kecamatan Banjar Kabupaten Buleleng - NGURAH ADI PUTRA MANDALA; DWI PUTRA DARMAWAN; I WAYAN WIDYANTARA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Financial Feasibility Analysis and Grapes Farming Sensitivity in Banjar Village, Banjar District, Buleleng Regency.Bali Grapes, especially those in Buleleng Regency, are one of the superior products of the region with a large potential to be developed. Bali Grapes have been cultivated for along time in several sub-districts, one of them in Banjar District. Grape farming issought to get maximum profit during its economic life. This study aims to: (1) Knows the feasibility of grape farming in the Banjar Village, Banjar District, BulelengRegency. (2) Knowing the sensitivity level of NPV, IRR, Net B/C, and Payback Periodon grapes farming in Banjar Village, Banjar District, Buleleng Regency. Locationselection is done purposively. The data used includes primary data and secondary data.Primary data were obtained from questionnaires and interviews. Secondary data wasobtained from various literatures and several related agencies. Data retrieval was carriedout in July to August 2018. The analysis carried out included farming feasibility: NPV,IRR, Net B/C, PP, and Sensitivity. The results showed that: (1) Grapes farming isfeasible to be developed financially, because the NPV value > 0, Net B/C > 1, IRR >applicable interest rates, and capital returns with a time limit of less than 8 years. (2)The sensitivity / sensitivity of grape farming occurs in the decline in the selling price ofwine, in the decline in production and in the increase in production costs, so that winefarming becomes inappropriate.